2003
DOI: 10.1093/brain/awg224
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids inhibit neurodegeneration in models of multiple sclerosis

Abstract: Multiple sclerosis is increasingly being recognized as a neurodegenerative disease that is triggered by inflammatory attack of the CNS. As yet there is no satisfactory treatment. Using experimental allergic encephalo myelitis (EAE), an animal model of multiple sclerosis, we demonstrate that the cannabinoid system is neuroprotective during EAE. Mice deficient in the cannabinoid receptor CB1 tolerate inflammatory and excitotoxic insults poorly and develop substantial neurodegeneration following immune attack in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
213
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(238 citation statements)
references
References 67 publications
16
213
1
7
Order By: Relevance
“…Cnpase is involved in RNA trafficking, splicing, and metabolism in the myelinating oligodendrocyte 30, 31, 32, 33. The severity of demyelination in EAE model is modulated by CB1 receptor 34, 35, which underpins the present findings. Furthermore, we reported lower Napepld expression in all groups fed with CPZ and this fact might indicate less AEA content.…”
Section: Discussionsupporting
confidence: 73%
“…Cnpase is involved in RNA trafficking, splicing, and metabolism in the myelinating oligodendrocyte 30, 31, 32, 33. The severity of demyelination in EAE model is modulated by CB1 receptor 34, 35, which underpins the present findings. Furthermore, we reported lower Napepld expression in all groups fed with CPZ and this fact might indicate less AEA content.…”
Section: Discussionsupporting
confidence: 73%
“…While the immunosuppressive effects of cannabinoids (Cabral and Vasquez, 1992;Morahan et al, 1979) and their modulatory activities on immune cell functions (Cabral and Mishkin, 1989;Fischer-Stenger et al, 1992;Klein et al, 1991) have been reported previously, there is recent evidence supporting the premise that cannabinoids also have anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998), and anti-tumor properties (GalveRoperh et al, 2000). Cannabinoids have been shown to be neuroprotective in a variety of in vitro and in vivo models of neuronal excitotoxicity (van der Stelt and Di Marzo, 2005;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…No difference in day of onset or peak clinical score was detected between wild-type and CB 1 receptor-deficient animals (Pryce et al, 2003). However, after EAE symptoms in wild-type animals had remitted, CB 1 receptor-deficient animals still had a high mean clinical score (Pryce et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Taking a more genetic approach to examining the cannabinoid system in EAE, Pryce et al (2003) induced EAE in wildtype and CB 1 receptor-deficient mice. No difference in day of onset or peak clinical score was detected between wild-type and CB 1 receptor-deficient animals (Pryce et al, 2003).…”
Section: Introductionmentioning
confidence: 99%